Estimation of Phagocytic Activity by Normal Human Peripheral Blood Mononuclear Cells on Various Oral Isolates of Candida Species: an in-vitro Study - Sreelakshmi, PJ; Harish, Kumar KS; Kuruvilla, Jacob; Theckel, Philip George (Journal of Medical Science, 2024)
Polymorphonuclear neutrophils (PMN) and mononuclear phagocytes represent an important first line and effector function in controlling Candida infections. The study aims to determine the in-vitro phagocytic activity of human peripheral blood mononuclear cells against oral isolates of Candida species and its antifungal susceptibility. The study also evaluates the degree of respiratory burst activity of PBMCs. Phagocytic and lytic indices by PBMCs were determined for Candida spp. The respiratory burst activity was evaluated using a nitroblue tetrazolium test. Antifungal disc diffusion susceptibility testing was performed.100 Candida were isolated, belonging to C. albicans, C. tropicalis, C. krusei and C. auris. The phagocytic and lytic indices of C. albicans were significant compared to the standard strain of C. albicans. C. tropicalis and C. krusei phagocytic index were significant, while the lytic index was insignificant compared to the standard strain. The inter-species comparison of both indices was not significant for the clinical isolates of Candida. A significant reduction in phagocytic activity was observed for clinical isolates of Candida spp. However, lytic activity was variable compared to the standard strain of C. albicans.